Spectroscopic Study of Co(II), Ni(II) and Cu(II) Complexes with Nitrogen and Sulphur Containing Schiff Base Ligands - Rai, B.K.; Sinha, Puja; Vidyarthi, S.N.; Singh, Vineeta (Asian Journal of Chemistry, 2011)
A series of Co(II), Ni(II) and Cu(II) Schiff base complexes of the general composition [M(TITPT)2X2] where M = Co(II), Ni(II) and Cu(II); TITPT= 2,3,4,5-tetrahydroindeno(1,2- d)thiazolo(3,2-a)[1,3]pyrimidine-(10H) thiosemicarbazone; X=Cl-, Br-, I- and NO3- were synthesized and characterized. The ligand and its Co(II), Ni(II) and Cu(II) complexes were formulated by elemental analyses, molar mass, infrared spectra, electronic spectra, magnetic susceptibility and molar conductance data. In the light of above studies it is proposed that the TITPT behaves as bidentate ligand and coordination takes place through azomethine nitrogen and thione sulphur atom of thiosemicarbazone moiety. The remaining positions of metal ions are satisfied by negative ions such as Cl-, Br-, I- and NO3- . The complexes were proposed to be octahedral in geometry.